Vademecum contemporary history Hungary : a guide to archives, research institutions, libraries, associations, museums and places of memorial / edited by, János M. Rainer, Judith M. Topits, Ulrich Mählert - Rainer, M. JánosTopits, Judit M.Mählert, Ulrich (1968-)
Contiene directorios de archivos, bibliotecas, museos, medios de información, asociaciones y centros de educación e investigación de Hungría